Kepemimpinan Kepala Sekolah dalam Mengembangkan Kegiatan Ekstrakurikuler Keagamaan di Sekolah Dasar Negeri 01 Lemito - Isma Tangahu; Lisdawati Muda (Pascasarjana IAIN Sultan Amai Gorontalo, 2020)
This study aims to determine how the headmaster's leadership in the development of religious extracurricular activities in State Elementary School, Lemito. This type of research is a qualitative study with a sociological managerial approach. The results showed: 1) religious extracurricular activities were carried out well in the form of: religious practices, reading and writing of the Koran and lightning boarding schools. 2) The nature of the principal's leadership in developing extracurricular activities is energetic in developing activities, intelligent controlling emotions and, able to motivate personal. The principal's leadership in developing religious extracurricular activities should not be separated from the steps of development. Because even though the headmaster of the school is very good in his leadership character, if without developmental steps such as planning, organizing, communicating and monitoring in religious extracurricular activities the program will not be maximized.